Phytochemical and biological studies on rare and endangered plants endemic to China. Part XIV. Structurally diverse terpenoids from the twigs and needles of the endangered plant Picea brachytyla. (January 2020) - Jiang, Wei; Xiong, Juan; Zang, Yi; Li, Junmin; Osman, Ezzat E.A.; Li, Jing-Ya; Zhou, Yu-Bo; Li, Jia; Hu, Jin-Feng
Abstract: A phytochemical investigation on the MeOH extract of the twigs and needles of the endangered plant Picea brachytyla led to the isolation and characterization of thirty-eight structurally diverse terpenoids. Seven of these molecules are previously undescribed, including three abietane-type (brachytylins A–C) and one labdane-type (brachytylin D) diterpenoids, an unseparated C-24 epimeric mixture of cycloartane-type triterpenoids (brachytylins E/F, ratio: 1:1), and a rare rearranged 12(1 → 6)- abeo -megastigmane glycoside (brachytylins G). Their structures and absolute configurations were determined by extensive spectroscopic (e.g., detailed 2D NMR and ECD) methods and/or X-ray diffraction analyses. All the isolates were evaluated for their inhibitory activities against the adenosine triphosphate (ATP)-citrate lyase (ACL) and the Src homology-2 domain containing protein tyrosine phosphatase-2 (SHP2). Among them, abiesadine J showed inhibitory effect against ACL, displaying an IC50 value of 17 μM. 3 S, 23 R -Dihydroxycycloart-24-en-26-oic acid exhibited inhibitory effect on SHP2, with an IC50 value of 19 μM. Meanwhile, 3 R*, 23 S* -dihydroxycycloart-24-en-26-oic acid was found to have inhibitory effects against both ACL and SHP2, with IC50 values of 16 and 12 μM, respectively. Graphical abstract: Seven undescribed terpenoids, brachytylins A–G, along with thirty-one related known compounds, were isolated and characterized from the endangered conifer Picea brachytyla . Some isolates were found to have inhibitory activities against ATP-citrate lyase (ACL) and the Src homology-2 domain containing protein tyrosine phosphatase-2 (SHP2). Image 1 Highlights: It is a preliminary phytochemical study on the endangered conifer Picea brachytyla . Seven undescribed terpenoids, brachytylins A–G, were isolated and characterized. The configuration of brachytylin A was secured by X-ray diffraction analysis. Brachytylin G possesses a rare 12(1 → 6)- abeo -megastigmane scaffold. Some isolates were found to have inhibitory effects against ACL and/or SHP2.